Faktor-Faktor yang Berhubungan dengan Tingkat Dismenorea di SMP Negeri di Yogyakarta - Arista Gunawati; Wenny Artanty Nisman (JURNAL KESEHATAN REPRODUKSI, 2021)
Background: : The prevalence of incidence primary dysmenorrhea in Indonesia reaches 72,89 %. The level of dysmenorrhea varied among teenage girls from mild, moderate, to severe pain. There are various factors affecting the level of dysmenorrhea include age, nutritional status, age of menarche student, age of menarche her mother, the pain menarche, menstrual cycle, duration menstruation, body condition before menstruation, dysmenorrhea frequency, duration dysmenorrhea and disruption of activity.Objective: To know the factors correlated with level of dysmenorrhea among students in one of Junior High School in Yogyakarta.Method: This was observational research with cross sectional study and instruments used were questionnaire.  This research conducted on Mei 2016. Total population was 195 students with 74 as minimum sample. Sampling technique used was purposive sampling and the study involved 94 students as sample.Results and Discussion: Factors associated with the level of dysmenorrhea were pain during menarche, dysmenorrhea frequency and disruption of the activities of the female students in one of the Junior High School in Yogyakarta. Factors not related to the level of dysmenorrhea were age, nutritional status, age of menarche student, age of menarche her mother, menstrual cycle, duration menstruation, body condition prior to menstruation and duration of dysmenorrhea of the female students in one of the Junior High School in YogyakartaConclusion: Factors associated with level of dysmenorrhea was pain of menarche, dysmenorrhea frequency and disruption of the activities of the female students. Keywords: dysmenorrhea level; menstruation; teenage girl.